Robotic-Assisted Thoracic Surgery Approach to Thoracic Endometriosis Syndrome with Unilateral Diaphragmatic Palsy - Abiah Jacob; Adeyemi Coker; Steven Aleksandar Stamenkovic (Case Reports in Surgery)
Endometriosis is characterized by endometrial-like glands and stroma outside the uterine cavity, affecting women of reproductive age. Thoracic endometriosis syndrome (TES) is an entity producing a range of clinical and radiological manifestations, including catamenial pneumothorax, haemothorax, haemoptysis, and pulmonary nodules within the thoracic cavity or on the diaphragm. TES symptoms are nonspecific, warranting a high degree of clinical suspicion. Management includes hormone replacement therapy, surgical management, or a combination of both. We present a case of a 37-year-old woman who presented with TES and unilateral diaphragmatic palsy, managed with robotic-assisted thoracoscopic surgery and hormone replacement.